Black Folklore as a Psychological Development in Ralph Ellison’s Invisible Man Characters - Touami, Ghoussoune; Aribi ,Brahim (Faculty of Letters and Foreign Languages Department of English, 2017)
The previous century’s concern in African American literature was about the quest for identity, self-awareness and a sense of being. Identity had known as a continuing development and had tempted many artists such as Richard Wright, W. E. B. Du Bois and Ralph Ellison. During Harlem Renaissance, the Blacks were seduced by the identity construction and showed their pride of their being and belonging to African roots. The present study has an analytical nature which examines the psychological development of the Ralph Ellison’s Invisible Man characters and the use of Black aesthetics as a means of expressing the self. It also explores the blacks’ identity and their experience through the analysis of the novel and aims to investigate the pivotal events and the major characters as well as their progression in the novel, so that the reader can learn the issues related to the characters’ life